New psychoactive substances in Poland. The analysis of policy responses and its effects - Bujalski, Michał; Dąbrowska, Katarzyna; Wieczorek, Łukasz (Alkoholizm i narkomania, 2017)
Introduction : The aim of this article is to analyse the process of creation and implementation of policy on new psychoactive substances (NPS) in Poland in the context of definitional and legal issues, social and market response, implementation of prevention programmes and scientific knowledge. New psychoactive substances and policy response in Poland : New psychoactive substances are a subject to both criminal and administrative law in Poland. Two definitions that refer to NPS and two lists on which they can be placed are currently in force: the annex to the Act on Counteracting Drug Addiction and the annex to the regulation of the Minister of Health. Changes in legislation and the expansion of the list of scheduled substances in 2009-2015 were accompanied by an increase in health risks while the initial success of the policy was diminished with the revival of the NPS market. Critical evaluation of new psychoactive substances policy in Poland : New psychoactive substances challenged nearly every aspect of drug policy in Poland, starting from definitional struggles, through establishing frames of intervention, monitoring and risk assessment, to institutional developments, risk communication, and treatment. The strong focus of NPS policy on the reduction of supply had its obvious shortcomings. The strategy proved to be time consuming and limited in its effectiveness. The NPS market changed dynamically and access to reliable knowledge on NPS was limited, whereas the policy network made of several institutions was flawed and lacked structural and financial resources. Conclusions : The new psychoactive substances phenomenon was based on individual efficacy and economic effectiveness, new technologies, developed logistics, flexibility and responsiveness of the NPS market according to consumer requirements. It posed a challenge for drug policy and a risk that cannot be effectively controlled with ‘traditional’ repressive policies.